SPIRIT Model: Conceptual Development of 21st Century Teacher Competencies Based on Systematic Literature Review - Muh. Nasrullah; Sitti Hardiyanti Arhas (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to identify and synthesize the dimensions of 21st-century teacher competencies through the Systematic Literature Review (SLR) approach based on the PRISMA protocol. The main focus of this study is to formulate a new conceptual framework that is more holistic and responsive to the demands of today's education. This study uses the Systematic Literature Review (SLR) approach, which is compiled based on the PRISMA. However, the results of the thematic readings also reveal the emergence of repeated implicit patterns regarding the importance of environmental sustainability, teacher welfare, learning innovation, and inclusive education. Based on the reflection on these findings, a new conceptual model was formulated called SPIRIT, an acronym for Sustainable, Professional, Innovative, Resilient, and Inclusive Teachers. The SPIRIT model offers a more integrative framework of teacher competencies, covering academic, social, emotional, and contextual dimensions. These findings not only broaden the understanding of the competence of today's teachers but also provide conceptual contributions that can be used in developing education policies, teacher education curricula, and ongoing professional training.